2023
DOI: 10.4103/ijo.ijo_3233_22
|View full text |Cite
|
Sign up to set email alerts
|

Study of the relationship between serum lipid levels and primary open-angle glaucoma

Abstract: Purpose: To determine the association between serum lipid levels and primary open-angle glaucoma (POAG). Methods: In this case-control study, 50 patients with POAG documented by clinical tests using standard ophthalmologic equipment and 50 age-matched controls were investigated. Twelve-hour fasting serum lipid profiles, including total cholesterol, serum triglycerides, low-density lipoproteins (LDLs), and high-density lipoproteins (HDLs), were compared between the cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Controversial results in the association between the conventional lipid parameters and POAG have been reported [13][14][15][16][17][18]. In this study, we observed a significant increase in the small granular subclasses of LDL (LDL3 and sdLDL) and the oxidized derivative oxLDL in POAG patients with elevated TC and/or LDL-C levels.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Controversial results in the association between the conventional lipid parameters and POAG have been reported [13][14][15][16][17][18]. In this study, we observed a significant increase in the small granular subclasses of LDL (LDL3 and sdLDL) and the oxidized derivative oxLDL in POAG patients with elevated TC and/or LDL-C levels.…”
Section: Discussionmentioning
confidence: 45%
“…Our previous study demonstrated that POAG patients had significantly higher fasting plasma triglycerides (TGs) but lower high density lipoprotein cholesterol (HDL-C) levels at recruitment as compared to the control subjects [8]. Other studies reported a higher prevalence of elevated total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) levels in POAG patients [13], and the risk of POAG is positively associated with elevated TC levels, while the treatment to reduce TC might decrease the risk of POAG [14,15]. In contrast, a negative correlation between HDL-C levels and the risk of POAG [16], an inverse association between hyperlipidemia and POAG, as well as a lack of correlation between the blood levels of TC, LDL-C, and HDL-C with POAG were also reported [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous results elucidated that their investigations delineate a significant correlation between elevated serum lipid concentrations and an augmented risk of POAG. The average levels of cholesterol, triglycerides, and LDL were significantly elevated in the case group versus the group, ascertained with a 95% CI, whereas the variance in HDL levels between the two groups did not present a statistically significant discrepancy (21) . The previous results underscored the profound linkage between elevated levels of cholesterol, LDL, and triglycerides, alongside reduced HDL, and their association with POAG.…”
Section: Discussionmentioning
confidence: 76%
“…Hyperlipidemia is associated with an increased risk of elevated IOP and glaucoma with poor mechanistic understanding (5, 6, 73, 74). Systemic cholesterol levels are closely related to glaucoma occurrence and IOP elevation (36). Interestingly, cholesterol-lowering statins lower IOP and reduce the incidence of glaucoma (8, 38).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that cholesterol and its biogenic pathway are closely related to POAG occurrence and IOP elevation. Glaucoma patients showed a significantly higher total cholesterol levels than patients without glaucoma (35) and meta-analysis reported that increased cholesterol levels are associated with a higher risk of glaucoma and IOP elevation (6). Our recent work provided evidence that the inactivation of the transcription factors sterol regulatory element binding proteins (SREBPs), involved in fatty acid and cholesterol biogenesis, significantly lowered intraocular pressure (7).…”
Section: Introductionmentioning
confidence: 99%